Influence of a knee brace intervention on perceived pain and patellofemoral loading in recreational athletes. (August 2016) - Sinclair, Jonathan K.; Selfe, James; Taylor, Paul J.; Shore, Hannah F.; Richards, Jim D.
Abstract: Background: The current investigation aimed to investigate the effects of an intervention using knee bracing on pain symptoms and patellofemoral loading in male and female recreational athletes. Methods: Twenty participants (11 males & 9 females) with patellofemoral pain were provided with a knee brace which they wore for a period of 2 weeks. Lower extremity kinematics and patellofemoral loading were obtained during three sport specific tasks, jog, cut and single leg hop. In addition their self-reported knee pain scores were examined using the Knee injury and Osteoarthritis Outcome Score. Data were collected before and after wearing the knee brace for 2 weeks. Findings: Significant reductions were found in the run and cut movements for peak patellofemoral force/pressure and in all movements for the peak knee abduction moment when wearing the brace. Significant improvements were also shown for Knee injury and Osteoarthritis Outcome Score subscale symptoms (pre: male = 70.27, female = 73.22 & post: male = 85.64, female = 82.44), pain (pre: male = 72.36, female = 78.89 & post: male = 85.73, female = 84.20), sport (pre: male = 60.18, female = 59.33 & post: male = 80.91, female = 79.11), function and daily living (pre: male = 82.18, female = 86.00 & post: male = 88.91, female = 90.00) and quality of life (pre: male = 51.27, female = 54.89 & post: male = 69.36, female = 66.89). Interpretation: Male and female recreational athletes who suffer from patellofemoral pain can be advised to utilise knee bracing as a conservative method to reduce pain symptoms. Highlights: First study to investigate the effects of knee bracing in recreational athletes with patellofemoral pain. Knee bracing improved patient reported knee pain symptoms and reduced patellofemoral loading. Recreational athletes who suffer from patellofemoral pain may wish to utilise knee bracing to attenuate their symptoms.